2016
DOI: 10.1021/acsnano.6b00094
|View full text |Cite
|
Sign up to set email alerts
|

A Process for Topographically Selective Deposition on 3D Nanostructures by Ion Implantation

Abstract: Area-selective atomic layer deposition (AS-ALD) is attracting increasing interest because of its ability to enable both continued dimensional scaling and accurate pattern placement for next-generation nanoelectronics. Here we report a strategy for depositing material onto three-dimensional (3D) nanostructures with topographic selectivity using an ALD process with the aid of an ultrathin hydrophobic surface layer. Using ion implantation of fluorocarbons (CFx), a hydrophobic interfacial layer is formed, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 41 publications
2
103
0
Order By: Relevance
“… 11 However, ALD typically leads to deposition on the entire surface, and therefore the process needs to be adapted to enable area-selective deposition. 7 , 12 15 To date, most of the efforts in the field of area-selective ALD include substrate patterning steps before the area-selective ALD. 12 , 16 , 17 On the other hand, in self-aligned fabrication, a partially processed device architecture is taken as the starting point, where patterning has been performed in a previous processing step.…”
mentioning
confidence: 99%
“… 11 However, ALD typically leads to deposition on the entire surface, and therefore the process needs to be adapted to enable area-selective deposition. 7 , 12 15 To date, most of the efforts in the field of area-selective ALD include substrate patterning steps before the area-selective ALD. 12 , 16 , 17 On the other hand, in self-aligned fabrication, a partially processed device architecture is taken as the starting point, where patterning has been performed in a previous processing step.…”
mentioning
confidence: 99%
“…However, preparation of conformal and thickness‐controllable nanocoatings on microstructured surfaces is more challenging. Recently, area‐selective atomic layer deposition has been developed to realize selective growth of thin films with excellent conformality, atomic scale thickness controllability, and large‐area uniformity . However, this technique requires complex steps and expensive equipment, and is only suitable for the formation of thin film on the nanostructured surfaces.…”
mentioning
confidence: 99%
“…More recently, plasma‐based processes have demonstrated a potential way to alter surface chemistry and affect ASD. Kim et al showed that ion implanted fluorocarbons could be used as a layer to reduce nucleation during ALD on planar features. Significantly, the process was extended to 3D nanofin structures where Pt deposition was shown on sidewall features while avoiding deposition on horizontal areas.…”
Section: Introductionmentioning
confidence: 99%